This is going to hurt [videorecording (DVD)] - Kay, Adam, 1980- (AMC Studios, 2022)
A young doctor feels stuck in a system which can seem like it's against him as he faces 97-hour weeks, life-and-death decisions, and so much gore all for a wage that barely pays for his parking meter.